Ubud Beauty and Wellness Day Spa Business Plan - Inderadi, Regina (2014)
The growth of spa businesses in Indonesia has motivates Ubud Spa corporation to establish a spa with a unique blend of the traditional and modern treatment by offering natural and herbal-rich services and products. Ubud Spa provides customers with a different atmosphere with a green-traditional concept of design for exterior and interior. The business will be set up as a sole proprietorship. Ubud Spa will only serve women customers. In addition, Ubud Spa offers additional services, such as Jamu drink which is made from herbs and spices that is freshly served in the minibar inside the venue. Ubud Spa has chosen a strategic place in The Icon Business Park, BSD City, Tangerang, Indonesia as its location for the business venture. Ubud Spa’s competitive edge is the method of customization of ingredients for treatments that are guaranteed to be free from chemicals such as parabens and preservatives. The survey we conducted was on aspects of the target customers and the market to ensure a highly feasible start-up business plan. This business plan has been developed prior to the opening of the spa business and following through with a five-year projection. The initial investment is 375,286,000 IDR; the profit is reached in the first year, which is shown with the BEP and positive cash flow. It is concluded that this business is feasible to be continued for implementation.